Pengaruh Financial Leverage, Likuiditas, Pertumbuhan Asset, dan Ukuran Perusahaan terhadap Beta Saham Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Desi Wury Handayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2014)
The purpose of this study is to investigate the influence of financial leverage, liquidity, asset growth, size on the beta stock in manufacturing companies in Indonesia Stock Exchange. The sample in this study is manufacturing companies listed in Indonesia Stock Exchange during the 5 periods (2008-2012). Total samples are 58 companies. The sample selection is done by using the method of stratified random sampling. The multiple linear regression analysis was used to test the hypothesis.This research found that asset growth has significant effect on systematic risk, while variable financial leverage, liquidity, sizedid not have significant effect on systematic risk. The purpose of this study is to investigate the influence of financial leverage, liquidity, asset growth, sizeon the beta stock in manufacturing companies in Indonesia Stock Exchange. The sample in this study is manufacturing companies listed in Indonesia Stock Exchange during the 5 periods (2008-2012). Total samples are 58 companies. The sample selection is done by using the method of stratified random sampling. The multiple linear regression analysis was used to test the hypothesis.This research found that asset growth has significant effect on systematic risk, while variable financial leverage, liquidity, sizedid not have significant effect on systematic risk.